Synthesis and magnetic characterization of magnetite particles embedded in mesoporous MCM-41 - Fellenz, Nicolás Antonio (2006)
A solid of 7.7 wt% iron-loaded MCM-41 was obtained by impregnating the mesoporous material with an Fe-carrying organic salt after subjecting the matrix to a silylation treatment. The Mössbauer and magnetic results show that the as-prepared composite is mainly made up of fine Fe3O4 particles that display a superparamagnetic relaxation at room temperature and block at ≈42 K. A percentage of ≈24% of the iron-containing phases is magnetically blocked at room temperature, and belongs to Fe3O4 that undergoes the Verwey transition. In addition, there is a minor Fe(III) phase that remains paramagnetic down to 4.2 K. © 2006 Elsevier B.V. All rights reserved.